PENGARUH PENDEKATAN PMRI DENGAN MENGGUNAKAN METOE KOLABORATIF TERHADAP HASIL BELAJAR SISWA SMP NEGERI 13 LUBUKLINGGAU - Lia Puspita Sari; Anna Fauziah; Dodik Mulyono (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to determine whether there is an effect of the PMRI learning model and approach using collaborative methods on the learning outcomes of class VIII students of SMP Negeri 13 Kota Lubuklinggau. This type of research was used in the form of a true experimental design with a pre-test-post-test control qroup design. The sampling technique is done by random or random. The instrument used is a description test. Data analysis techniques in this study used prerequisite tests in the form of normality and homogeneity tests and hypothesis testing using the t-test. The results of the study show that there is a significant influence on the use of the PMRI approach using collaborative methods on student learning outcomes in class VIII SMP Negeri 13 Lubuklinggau City. This is evidenced by the results of the t-test with a significance level of 5%, diperoleh > (6,99 > 1,67). so it can be concluded that there is a significant influence of the PMRI approach learning model using collaborative methods on the mathematics learning outcomes of Grade VIII students of SMP Negeri 13 Kota Lubuklinggau for the 2022/2023 Academic Year. The average score of students' mathematics learning outcomes after being treated in the experimental class was 71.21 and the control class was 35.97.